THE APPLICATION OF BLOCKCHAIN FOR SMART CONTRACTS IN MURABAHAH FINANCING: A SHARIA COMPLIANCE AND LEGAL ENFORCEABILITY STUDY - Nopita Sari; Nurul Ain Safrizon; Basarudin Basarudin; Adam Idris (Yayasan Adra Karima Hubbi, 2025)
The increasing adoption of blockchain technology in Islamic finance has prompted growing interest in its application for smart contracts within murabahah financing structures. The digital transformation of financial transactions raises important questions regarding Sharia compliance, contractual validity, and legal enforceability in decentralized systems. This study aims to examine how blockchain-based smart contracts can enhance transparency, efficiency, and trust in murabahah financing while maintaining strict adherence to Islamic legal principles. A qualitative-doctrinal research method was employed, integrating analysis of classical fiqh al-mu’?mal?t with contemporary regulatory frameworks governing digital transactions and smart contract implementation. The study utilized comparative analysis of existing blockchain platforms and Islamic financial models to identify areas of alignment and potential conflict. The findings indicate that blockchain technology supports murabahah transactions by automating contract execution, eliminating asymmetrical information, and ensuring compliance with Sharia requirements for ownership transfer and cost disclosure. However, challenges remain in achieving legal recognition of decentralized contracts within conventional judicial systems. The study concludes that blockchain-based smart contracts can be considered Sharia-compliant when developed under proper legal supervision and governance mechanisms, offering a promising pathway for digital transformation in Islamic finance.